Digestibilidade da matéria seca, proteína bruta e energia bruta da silagem de milho associada ao concentrado, por meio de ensaios in vivo e in vitro - Secco De Oliveira, Mauro Dal [UNESP]; Moraes Sampaio, Alexandre Amstalden [UNESP]; De Figueiredo Vieira, Paulo [UNESP]; Banzatto, David Ariovaldo [UNESP] (My University, 1997)
A study was made to compare dry matter, crude protein and gross energy digestibility of corn silage, associated to concentrate, through in vitro and in vivo digestion techniques. A completely randomized design was used, with two treatments and nine replications, involving three assays. The in vivo digestion assay was conducted with 12 Holstein heifers, on a 24 h permanent sample collection. The in vitro digestion assay was achieved with three collection methods: manual (M), vacuum pump (VP) and nasoesophagic (N). The collection methods VP and M can be used to determine the dry matter digestibility, instead of in vivo method, for the present study ration. The digestion methods influenced the DM, CP and GE digestibility for the studied ration.
Dry matter, crude protein and gross energy digestibility of corn silage and concentrate mixture through in vivo and in vitro digestion assays
Keywords: Bovine; Diet; Forage; Ruminal content